EVALUATION OF AN AYURVEDIC FORMULATION IN THE MANAGEMENT OF ESSENTIAL HYPERTENSION IN ELDERLY PATIENTS - Chaudhary, Vijay; Rohila, Rajnikant (International Journal of Ayurveda and Pharma Research, 2015)
Introduction: Hypertension is emerging as a pandemic in the society. Though a lot of potent antihypertensive drugs are available today but none of them is free from untoward effects. Especially the elderly population poorly tolerates these drugs. Objective: This study was conducted to clinically evaluate the efficacy of an Ayurvedic formulation in the management of essential hypertension in elderly patients. Materials and Methods: 45 patients of either sex of stage-I essential hypertension in the age group of 60-90 years were registered for the present study. Patients with stage-II hypertension, and secondary hypertension were excluded from study. Registered patients were randomly divided into two groups. In group-I patients were managed with Tagar Churna, Gokshur Churna and Triphla Churna. Group-II patients were managed with a standard calcium channel blocker drug Amlodipine. The duration of trial was 30 days. Observations: After one month of therapy statistically highly significant reduction in systolic B.P., diastolic B.P. mean arterial B.P. and pulse pressure was observed in both groups. Pulse rate was statistically significantly reduced in group-I patients. Biochemical studies revealed a beneficial effect on serum lipid profile in group-I patients whereas in group-II patients it remained unchanged. Conclusion: It is evident from results of the study that combination of Tagar and Gokshura along with Triphala Churna possess potent antihypertensive activity. Combination of trial herbs appear to be safe for elderly hypertensive patients when given in mentioned doses and duration as no untoward effect of therapy was observed during the study period.